Desempenho agronômico de linhagens de tomate para processamento industrial visando consumo in natura - Peixoto, Joicy Vitória Miranda (2016)
The tomato is an important crop in both the national scene, and internationally, being its fruits among the most consumed in the world. These have nutritional importance, a source of several essential nutrients for a balanced diet as vitamin C, pro-vitamin A (betacarotene) and antioxidants (lycopene and other carotenoids). The social and economic importance of culture is associated with the generation of employment and source of funds for family. Given the benefits of tomato and its relevance in the country objective of this study was to characterize 25 genotypes of industrial tomato as the morphological aspects (number of leaf branches and floral racemes), productive and nutritious, and to select those likely to fruit cultivation to consumption "in natura" aimed at producing hybrids. The evaluation of the number of branches leaf and floral racemes allowed to conclude that the first variable positively influences the second, providing increased productivity. The lines CVR 1, CVR 3, CVR 4, CVR 5, CVR 21 and CVR 22 have an aptitude for genetic improvement of tomato, these being the higher productivity. Furthermore, it is concluded that lines including the CVR 8 are suitable for consumption "in natura", being that they produce fruits with soluble solid content above three degrees brix, oblong format, pH and vitamin C content in normal amount. The CVR 22 lineage produces tastier fruits due to better ratio between soluble solids and titratable acidity. The CVR 3 and CVR 8 lines yield fruits of higher acidity and lower pH, and accentuated red color, are indicated for the genetic improvement of industrial tomato.